Applying A* Path Planning Algorithm Based on Modified C-Space Analysis - Raheem, Firas A.; Hussain, Asmaa A. (Al-Khwarizmi Engineering Journal, 2018)
In this paper, a modified derivation has been introduced to analyze the construction of C-space. The profit from using C-space is to make the process of path planning more safety and easer. After getting the C-space construction and map for two-link planar robot arm, which include all the possible situations of collision between robot parts and obstacle(s), the A* algorithm, which is usually used to find a heuristic path on Cartesian W-space, has been used to find a heuristic path on C-space map. Several modifications are needed to apply the methodology for a manipulator with degrees of freedom more than two. The results of C-space map, which are derived by the modified analysis, prove the accuracy of the overall C-space mapping and construction, and then a successful and guaranteed path from a start to goal configuration has been obtained without any collision probability. The results had been achieved by (Matlab R2015a) software, which run on Intel (R) Core (TM) i3-3120M CPU.